2021
DOI: 10.48550/arxiv.2107.12026
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hemodynamic Deconvolution Demystified: Sparsity-Driven Regularization at Work

Abstract: Deconvolution of the hemodynamic response is an important step to access short timescales of brain activity recorded by functional magnetic resonance imaging (fMRI). Albeit conventional deconvolution algorithms have been around for a long time (e.g., Wiener deconvolution), recent stateof-the-art methods based on sparsity-pursuing regularization are attracting increasing interest to investigate brain dynamics and connectivity. This technical note revisits the main concepts underlying two main methods, Paradigm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 93 publications
0
9
0
Order By: Relevance
“…Some effects of the regularization constant for the closed form solution have been tested and described in the appendix section. Some of the earlier studies have shown SNR based regularized constant value selection techniques, mainly targeted for iterative L1 regularization [Uruñuela et al, 2021].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some effects of the regularization constant for the closed form solution have been tested and described in the appendix section. Some of the earlier studies have shown SNR based regularized constant value selection techniques, mainly targeted for iterative L1 regularization [Uruñuela et al, 2021].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, deconvolution models have also been used to identify underlying neural events from the observed BOLD time series [23,24,25]. Commonly, hemodynamic deconvolution models use lasso regularization (L1 regularization) which results in temporally sparse neuronal activity [26,27,28]. One of the main goals was to obtain a obtain a continuous visualization of the decision-making process while the output of L1 regularization was sparse.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, extending the proposed stability selection technique to other formulations of the hemodynamic deconvolution problem, such as the voxel-wise (i.e., univariate) single-echo (Gaudes et al, 2013; Uruñuela et al, 2020), univariate multi-echo (Caballero-Gaudes et al, 2019), or low-rank and sparse formulations (Uruñuela et al, 2021b; Cherkaoui et al, 2021), is relatively straightforward. Moreover, considering that synthesis-based models, such as Paradigm Free Mapping (Gaudes et al, 2013), and analysis-based models, such as Total Activation (Karahanoğlu et al, 2013), for temporal hemodynamic deconvolution yield identical results (Uruñuela et al, 2021a), and the fact that a multi-echo formulation provides higher accuracy for deconvolution (Caballero-Gaudes et al, 2019), we argue that the proposed MvME-SPFM method with stability selection should result in more reliable estimates of the activity-inducing signal.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the multivariate formulation could exploit complimentary multimodal information such as structural connectvity from diffusion-based MRI data (Bolton et al, 2019b). In addition, the proposed formulation can be easily adapted to model the changes in neuronal activty in terms of its innovations, which can be more appropiate to capture sustained BOLD events (Uruñuela et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%
“…This issue has been addressed by (Karahanoglu et al, 2013;Karahanolu and Van De Ville, 2015;Uruuela et al, 2021), where the authors have defined the term activity-inducing signal, which, as the name suggests, comprises any input signal that induces hemodynamic activity. We will refer to activity-inducing signals as source signals in the rest of this paper, which steers the reader to broader terminology not only used in biomedical signal processing, but also in acoustics and telecommunications (Naik and Wang, 2014), and emphasizes that recorded output data are sourced by such signals.…”
Section: Introductionmentioning
confidence: 99%